The Impact of Social Media Marketing – Study from Malaysia Perspective - Kumarashvari, Subramaniam; Nasreen, Khan (INTI International University, 2019)
In Malaysia, banks are mindful of the power of social media, and are active on social media platform, because they want to meet the rising customers’ expectations for personalization and demonstrating value to them. On the other hand, fierce commercial competition, extensive customers demand and new innovations forced organizations to constantly seek uniqueness in their offering that can cultivate customer loyalty. Nevertheless, banks are still struggling to cultivate customer loyalty and empirical studies conducted from the social media perspective seems to be equivocal. As such, a study investigating the power of social media involving three variables, namely functional value, social value and customer experience took place with population sampling represented by domestic bank Facebook community members. The rigorous empirical study took place between the time period of April 2019 – June 2019. 90 completed questionnaires were used for the data analysis using the Smart PLS 3.0. The results indicated that social value and customer experience have direct effect on customer loyalty and customer experience has the most significant effect. Nevertheless, functional value does not have direct effect on customer loyalty. Moreover, customer experience has mediation effect between social and functional value leading to customer loyalty. The study aims to give an insight to the bank practitioners on how they can prepare when dealing with customer in the digital platform. As for the body of knowledge the empirical study provides an evidence the importance of customer experience and social value and close the gap between the value-attitude-behaviour in the digital setting.